The Nature of Science and Its Role in the Formation of the Modern Knowledge Paradigm - Ali Malkan Amin; Ajeng Purnama Dewi; Euis Siti Solihah; Nabila Aulia Putri; Salsa Larasati; Siti Maulidah; Maspuroh (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
Science is a conscious effort to research, search, and improve human understanding of various aspects of reality in the human field. These aspects are limited by accurate formulas of words. Science provides confidence, limiting the level of opinion and confidence in science derived from its restrictions. Specific scientific fields. Considered from the point of view of philosophy, science is formed because people try to think that they have knowledge. Science is a product of Istemology. Science is a conscious effort to explore and discover various aspects of the reality of the human world and to improve human understanding. These aspects are limited by accurate formulas of words. Science gives confidence, limits its views, and gains confidence in science from its limitations.